Indywidualizacja w polskiej dydaktyce języków obcych okresu 1919-1939 - Maria Harbig, Anna (Neofilolog, 2011)
Attempts at individualisation in teaching appeared in the Polish didactics for foreign languages during the interwar period following the influence of the „new school” concept, as propagated by the reformation move-ments in American and European education. On the basis of teaching curriculums, practical reports and theoretical contemplations from the years 1919-1939, the article shows the way the then contemporary teach-ers of foreign languages understood the notion of individualisation, their arguments for its necessity and also the ways the were trying to adapt the new individualising methods of work and forms of organising lessons for their home environment.